Transgender care : recommended guidelines, practical information, and personal accounts - Israel, Gianna E., 1963- (Temple University Press, 1997)
By empowering clients to be well informed medical consumers and by delivering care providers from the straitjacket of inadequate diagnostic standards and stereotypes, this book sets out to transform the nature of transgender care. In an accessible style, Gianna Israel and Donald Tarver discuss the key mental health issues, with much attention to the vexed relationship between professionals and clients. They propose a new professional role, that of the "Gender Specialist." The authors have also provided useful listings of organizations, centers, and World Wide Web sites. Transgender Care has been reviewed by a national committee of professionals and consumers, some of whose members contributed essays in the second part of the book.